The paradox of adaptive responses and iso-effect per fraction: The history of dose fractionation symposium: September 2015, RRS annual meeting. (28th July 2018) - Blyth, Benjamin J.
Abstract: Purpose: Despite decades of research into radiation-induced adaptive responses, where prior irradiation changes the response to subsequent irradiations, the field of radiation oncology relies upon models of tumor control that assume that each radiation therapy fraction reproduces the same effect, known as iso-effect per fraction. Can these radiobiology principles both be true, forming a paradox or is only one of them right? Here, the apparent coexistence of these two contradictory observations is considered, examining how adaptive responses might apply in radiotherapy scenarios that are inconsistent with the majority of adaptive response experimental designs. Conclusion: While the iso-effect per fraction assumption would preclude the observation of adaptive responses for cells survival after radiotherapy fractions, this does not preclude the observation of adaptive responses for other endpoints. Adaptive responses for cell survival might also manifest without invalidating the iso-effect principle in practical terms. It may also be the case that instances of both phenomena can be observed under different conditions, but not at the same time.